2009
DOI: 10.1021/la803898g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Colistin on Surface Ultrastructure and Nanomechanics of Pseudomonas aeruginosa Cells

Abstract: Chronic lung infections in cystic fibrosis patients are primarily caused by Pseudomonas aeruginosa. Though difficult to counteract effectively, colistin, an antimicrobial peptide, is proving useful. However, the exact mechanism of action of colistin is not fully understood. In this study, atomic force microscopy (AFM) was used to evaluate, in a liquid environment, the changes in P. aeruginosa morphology and nanomechanical properties due to exposure to colistin. The results of this work revealed that after 1 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
71
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 46 publications
8
71
0
1
Order By: Relevance
“…Thus, based on these observations, it was concluded that convoluted or irregular surfaces were the result of experimental artifacts. Recently, structural changes in bacterial surface morphology upon challenging bacteria with antibacterial agents have been reported (19)(20)(21)47). As an example, the smooth membrane structure of wild-type E. coli develops blebs and wrinkles after exposure to antimicrobial BP100 and pepR peptides, as revealed by AFM of air-dried bacterial samples (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, based on these observations, it was concluded that convoluted or irregular surfaces were the result of experimental artifacts. Recently, structural changes in bacterial surface morphology upon challenging bacteria with antibacterial agents have been reported (19)(20)(21)47). As an example, the smooth membrane structure of wild-type E. coli develops blebs and wrinkles after exposure to antimicrobial BP100 and pepR peptides, as revealed by AFM of air-dried bacterial samples (19).…”
Section: Discussionmentioning
confidence: 99%
“…This membrane dependent mechanism of antibacterial action was observed in Pseudomonas aeruginosa after exposure to colistin, an antibacterial peptide (20). This treatment resulted in an originally smooth surface changing to a wrinkled or rugose phenotype (20). Interestingly, a number of Gram-negative bacteria naturally show convoluted or rugose surfaces (22)(23)(24).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, nanomechanical approaches study the effect of drugs on Pseudomonas aeruginosa, the causative agent of chronic lung infections in patients affected by cystic fibrosis (19).…”
Section: Nanotechnology In Medicine: Physical Foundations Of Nanomedimentioning
confidence: 99%